Diseño e implementación de módulos de entrenamiento con aplicaciones de control Pid de un caldero de una cámara de estabilidad utilizando la interface ni MYDAQ y el software LABVIEW - Arteaga Marín, Darwin de Jesús (2014)
The next project is about the design and implementation of 5 training modules, in which you can simulate several common processes in industrial plants such as control and monitoring system temperature, level, among others, and may make the PID (Proportional-Integral-Derivative) control of the process to characterize the stability chamber designed. These didactic application modules allow to optimize assembly time and wiring for the implementation of the elaborated practices, so the system allows the development of new industrial applications, applying the knowledge acquired in the subjects taught at the career of Electronics Engineering. The fundamental basis for this project is the interface myDAQ and NI LabVIEW graphical programming software. With these modules the application didactic teaching-learning process will be strengthened in the area of automatic control of the race. It is noteworthy to mention that in addition to the construction project of a structure of a camera kettle to demonstrate the stability for PID control system temperature was performed.